Dy3+ and Mn4+ Ions Co-Doped Stannate Phosphors for Applications in Dual-Mode Optical Thermometry - Zaifa Yang; Zhide Wang; Yi Su; Wenyue Zhang; Yu Zheng (Molecules)
In order to break through the limitations of the application of traditional temperature measurement technology, non-contact optical temperature sensing material with good sensitivity is one of the current research hotspots. Herein, a series of Dy3+ and Mn4+ co-doping Mg3Ga2SnO8 fluorescent materials were prepared successfully, and the crystal structure, phase purity, and morphology of the synthesized phosphors were comprehensively investigated, as well as their photoluminescence properties, energy transfer, and high-temperature thermal stability. The two pairs of independent thermally coupled energy levels of Dy3+ ions and Mn4+ ions in Mg3Ga2SnO8 are utilized to realize the dual-mode optical temperature detection with excellent performance. On the one hand, based on the different ionic energy level transitions of 4F9/2→6H13/2 and 2Eg→4A2g responding differently to temperature, two emission bands of 577 nm and 668 nm were chosen to construct the fluorescence intensity ratio thermometry, and the maximum sensitivity of 1.82 %K−1 was achieved at 473 K. On the other hand, based on the strong temperature dependence of the lifetime of Mn4+ in Mg3Ga2SnO8:0.06Dy3+,0.009Mn4+, fluorescence lifetime thermometry was constructed and a maximum sensitivity of 2.75 %K−1 was achieved at 473 K. Finally, the Mg3Ga2SnO8: 0.06Dy3+,0.009Mn4+ sample realizes dual-mode optical temperature measurement with high sensitivity and a wide temperature detection range, indicating that the sample has promising applications in optical temperature measurement.